EVALUASI LAHAN UNTUK PENGEMBANGAN KAWASAN PERMUKIMAN DI DUSUN TELAGA KODOK NEGERI HITUMESSING KECAMATAN LEIHITU KABUPATEN MALUKU TENGAH - Rusman, Rusman; Latupapua, Andrias Izaac; Puturuhu, Ferad; Luhukay, Marcus (MAKILA, 2024)
Research on Land Evaluation for Residential Development in the Telaga Kodok Hamlet area has been conducted with the aim of determining the suitability classes of residential land and identifying limiting factors. The land characteristics studied include slope, effective depth, flooding and ponding, drainage, rock, and soil texture. The weight of each characteristic was analyzed using the Analytic Hierarchy Process (AHP). The analysis results indicate that there are 112.07 hectares (29.94%) of highly suitable residential zones, 166.67 hectares (44.53%) of moderately suitable zones with limiting factors such as moderate depth, poor drainage, and fine texture; 92.03 hectares (24.59%) of marginally suitable residential zones with limiting factors like steep slopes and fine texture; and 3.55 hectares (0.94%) of zones unsuitable for residential development.